Distributional effects of immigration and imperfect labour markets - Julian Costas-Fernandez; Simon Lodato (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2023)
We present evidence whereby immigration increases labour productivity while reducing the labour share, thus redistributing income from workers to employers. This result is unlikely in competitive markets with skill-neutral capital, where labour share is orthogonal to immigration shocks in the long run. Instead, our empirical evidence better matches predictions from imperfect labour market models where immigrant and native workers are heterogeneous in both skills and labour supply elasticities.
Keywords: D33; J21; J24; J42; J61; O47; 330; Immigration; Productivity; Labour Share; Imperfect Labour Markets; FactorIncome Distribution